2001
DOI: 10.1054/bjoc.2001.1743
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of hypoxia to metastatic ability in rodent tumours

Abstract: SummaryThe relationship between tumour oxygenation in vivo and metastatic potential was investigated in 2 rodent tumour models, KHT-C fibrosarcoma and SCC-VII squamous cell carcinoma. The oxygen status in these rodent tumours transplanted intramuscularly in syngeneic mice was measured using the Eppendorf pO 2 Histograph. The results indicate a considerable heterogeneity in oxygenation between individual tumours within each tumour cell line. At different tumour sizes, animals were killed and lung lobes were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 32 publications
(51 reference statements)
3
54
0
2
Order By: Relevance
“…Indeed, a number of experimental studies have now shown that anti-angiogenic therapies may increase the tendency of tumors to fragment and invade surrounding host tissue. (e.g., Sakamoto (1987), Rubinstein et al (2000), DeJaeger et al (2001), E. Rofstad and Halso (2002), Seftor et al (2002), Lamszus et al (2003), and Bello et al (2004).) Conversely, we found that increasing the nutrient levels in the microenvironment leads to greater morphological stability and increased compactness of the tumor, thereby rendering the tumors more resectable.…”
Section: Discussion and Future Workmentioning
confidence: 41%
“…Indeed, a number of experimental studies have now shown that anti-angiogenic therapies may increase the tendency of tumors to fragment and invade surrounding host tissue. (e.g., Sakamoto (1987), Rubinstein et al (2000), DeJaeger et al (2001), E. Rofstad and Halso (2002), Seftor et al (2002), Lamszus et al (2003), and Bello et al (2004).) Conversely, we found that increasing the nutrient levels in the microenvironment leads to greater morphological stability and increased compactness of the tumor, thereby rendering the tumors more resectable.…”
Section: Discussion and Future Workmentioning
confidence: 41%
“…A number of experimental studies have recently shown that anti-angiogenic therapies may have this result [180,177,61,173,185,122,24]. Conversely, we found that increasing nutrient levels leads to greater morphological stability and increased tumor compactness, thereby rendering some tumors more resectable.…”
Section: Discussionmentioning
confidence: 51%
“…This includes the application of mathematical and empirical methods to quantify the competition between cell substrate gradient-related pro-invasion phenomena and molecular forces that govern proliferation and taxis, and forces opposing invasion through cell adhesion. The latter, under normoxic conditions, often enforce compact non-infiltrative tumor morphology while local oxygen gradients promote invasion [190,156,185,120,160,122,24,177,173,174,61,55,74,135]. Interactions between cellular proliferation and adhesion and other phenotypic properties may be reflected in both the surface characteristics, e.g., stability, of the tumor-host interface and the growth characteristics of tumors [59,55,74,87,135].…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is now established that the presence of oxygen-defi cient or hypoxic cells can not only lead to therapeutic resistance in preclinical tumor models but also have a detrimental effect on the ability to control human malignancies treated with curative intent (Hoeckel et al, 1993;Nordsmark, Overgaard and Overgaard 1996;Brizel et al, 1999, Brown andGiaccia, 1998;Horsman and Overgaard, 2002). Importantly, physiological pressures exerted by the tumor microenvironments also contribute to processes that favor malignant progression (Young, Marshall and Hill, 1988;Hill, 1990;Giaccia, 1996), oncogenesis (Giaccia, 1996;Graeber et al, 1996) and potential for metastatic spread (Young, Marshall and Hill, 1988;Hill, 1990;De Jaeger, Kavanagh and Hill, 2001;Brizel et al, 1996).…”
Section: Impact Of Tumor Microenvironments On Cancer Managementmentioning
confidence: 99%